Psychological factors and psychosocial interventions for cancer related pain - Ciucă Andrada; Băban Adriana (Sciendo, 2017)
The present paper is aimed at briefly presenting psychological factors involved in cancer related pain and what psychosocial interventions are efficient in reducing it. Cancer related pain is a complex experience and the most integrative and recommended approach is the biopsychosocial model. It has been proved that chronic pain is more strongly related to psychological factors than to treatment or illness related factors. Psychological factors influencing pain experience can be intuitively grouped starting with awareness of pain (i.e., attentional factor), then with evaluation of pain (i.e., cognitive factors) which is leading to feelings (i.e., emotional factors), and behaviours (i.e., coping strategies) regarding pain. Psychosocial interventions (i.e., skill based and education based interventions) have strong evidence that is effective in reducing cancer related pain.